O que as crianças nos ensinam em suas andanças errantes pelas ruas da cidade e pelos centros de referência especializados da assistência Social - Guarnier, Franciely da Costa (2016)
We intend to share in this dissertation experiences lived with children, considering the history of public policies with which we operate in our professional practice and the knowledges that guide our doing. The proposal was driven by the construction, along with the boys and girls in attendance in Specialized Reference Center of Social Assistance of Vitória / ES (SRCSA), of a search device that gives visibility to the memory of the children on the streets, seeking variant experiences of social actors that traditional history has lefted out. In this sense, we dare to narrate appointments with social care professionals that said about the reduction of the number of children and young people on the streets followed by SRCSA; with two young people who had their trajectories through the streets, the city, throught their daily experiences, the relationship built with the equipment of social assistance, with the workshops, with the other that cross through their experiences, with us that were with them looking for new entries and new elaborations of their experiences; the activation of the memory built with the appointments in Children and Adolescents Care Day Centre, the meeting and reunion with Joana; with the very process of searching; with the authors we read; with the research team of which we are part; with the streets we walked demanding for boys and girls, etc. To build narratives from what was proposed by Walter Benjamin, we realized the invention of a new world that does not cease with modernity and its barbarities. The movement of immanent differentiation to life does not cease, and to be thrown into poverty experience that says a start from scratch, we are called to invent new arrangements, new bonds, new networks, that is new ways of acceptance of otherness. In this sense, we reaffirm a bet on the hosting maybe no longer anchored in tradition, but in the affections we are from the meetings with the other.